IMPLEMENTASI FRANCHISE BERBASIS SYARI`AH DI SEKTOR UMKM - Dijan Novia Saka (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2017)
Franchise is a business which widely targeted by the businessmen. Small and Medium Enterprises (SMEs) in the field of franchise business has a very good prospect for the economy in Indonesia. Franchise business is very diverse types, we must be careful to choose the franchisor to assist us in starting a franchise business. Although we are under the guidance of the franchisor, we also need to be more innovative to find a new business form of this franchise business. In Karangrejo Village Kandat Sub district Kediri Regency has the leading SMEs in the form of handicraft which called jaranan handicraft. But the craftsmen have not run a franchise in the field of jaranan handicraft. So it is very appropriate to apply sharia-based franchise for SMEs jaranan handicraft in the village. It is because by opening a sharia-based franchise business will provide many benefits, among others, the business will be more advanced, product marketing can be expanded, product quality can be improved, the price of its products can be stable and of course the income can increase. From the results of existing data analysis, the sharia-based franchise is very appropriate run in the SME sector in order to improve the economy and reduce unemployment. Because the franchise that applies the basic principles of sharia economy has advantages that are not owned by franchise in general. Shariabased franchises can survive in uncertain or uncertain economic conditions.